Horizontal Equity for Disabled People: Incapacity from Accident or Illness - Stephens, Robert (Victoria University of Wellington Law Review, 2004)
The current dual system of benefit provision and service delivery for disabled people has led to substantial horizontal inequities between those on the ACC register and those receiving income tested social security benefits. Whilst there are often distinct differences in the nature of the clientele between these groups, they often have similar requirements, but can receive quite different treatment. The Disability Strategy offers the prospect that a more unified system will be developed, initially in terms of service provision, especially rehabilitation and access to health care. The move to a combined benefit structure raises issues about the fundamental nature of social security, though equality of access to second and third tier benefits should minimise the degree of conflict between earnings related and flatrate benefits. From the perspective of disabled people, the major issue is access to nonincome support, ranging from access to equipment to health care, education and employment.